Corynoneura Winnertz from East Asia, with a systematic review of the genus (Diptera: Chironomidae: Orthocladiinae) - Fu, Yue; Sæther, Ole A.; Wang, Xinhua (Zootaxa, 2009)
Nine new species of Corynoneura Winnertz, C. confidens sp. n., C. cylindricauda sp. n., C. inefligiata sp. n., C. korema sp. n., C. latusatra sp. n., C. macdonaldi sp. n., C. medicina sp. n., C. nankaiensis sp. n. and C. prominens sp. n. are described and illustrated as males. C. arctica Kieffer, C. edwardsi Brundin, C. ferelobatus Sublette et Sasa, C. gratias Schlee, C. lobata Edwards, C. scutellata Winnertz and C. yoshimurai Tokunaga are classified based on Chinese specimen. Ten Japanese species: C. fujiundecima Sasa, C. ginzanquinta Sasa et Suzuki, C. inawapequea Sasa, Kitami et Suzuki, C. kibunelata Sasa, C. kibunespinosa Sasa, C. kisogawa Sasa et Kondo, C. seiryuresea Sasa, Suzuki et Sakai, C. sorachibecea Sasa et Suzuki, C. tokarapequea Sasa et Suzuki, C. tokaraquerea Sasa et Suzuki are reexamined based on the holotypes. C. ginzanquinta Sasa et Suzuki is transferred to the genus Thienemanniella Kieffer. A preliminary estimate of the phylogenetic relationships of the sufficiently known males is given. A key to the sufficiently known males of Corynoneura is provided.